Inhibition of CD44 attenuates pressure overload-induced cardiac and lung inflammation, fibrosis, and heart failure progression. (25th November 2020) - Weng, X; Yue, W; Shang, L; Wang, D; Xu, Y; Chen, Y; Ge, J
Abstract: Background: Inflammation contributes to heart failure (HF) development and progression. CD44 is a member of the hyaluronate receptor family of cell adhesion molecules, which regulates tissue inflammation and fibrosis through modulating macrophage and lymphocyte migration and homing in several diseases. Here we evaluated the role and cellular mechanism of CD44 in regulating transverse aortic constriction (TAC)-induced HF development and progression in mice. Methods and results: C57/B6 background CD44 KO and wild type mice (6–8 weeks) were subjected to TAC to evaluate the effect of CD44 on the development of TAC-induced LV hypertrophy and cardiac dysfunction. Due to the rapid response to TAC, Balb/c mice (6–8 weeks) were used to determine the effect of CD44 on the progression of TAC-induced congestive heart failure. We found that CD44 expression is dramatically increased in left ventricular (LV) tissues obtained from HF patients and mice. While CD44 gene knockout (KO) has no detectable effect on cardiac structure and function under control conditions, CD44 KO mice were protected from TAC-induced LV inflammation, fibrosis, hypertrophy, dysfunction, and lung remodeling as compared with wild type mice. In addition, we found that inhibition of CD44 signaling with blocking antibodies (Abs) significantly attenuated the transition from LV failure to lung remodeling, and right ventricular hypertrophy in mice with existing HF. Conclusions: These data identify an important role of CD44 in attenuating cardiac and lung inflammation, fibrosis, HF development, and HF progression, suggesting that inhibition of CD44 signaling may be useful in preventing and treating HF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Chinese National Natural Science Foundation Grants and American Heart Association